Solar thermal decoupled water electrolysis process II: An extended investigation of the anodic electrochemical reaction. (18th May 2018) - Nudehi, S.; Larson, C.; Prusinski, W.; Kotfer, D.; Otto, J.; Beyers, E.; Schoer, J.; Palumbo, R.
Highlights: We have quantified the anodic reaction kinetics of CoO. We developed a 3-D finite element model of the electrolysis process. We suggest a path toward the commercialization of the process. Abstract: We examined the kinetic and transport processes involved in the production of H2 from water with Co 2+ as the electroactive species being oxidized at a Ni electrode in 40 wt% KOH at 318 K. The relevant transport parameters such as electrochemical rate constants, transfer coefficients, diffusion coefficients, and adsorption coefficients were estimated from a combination of cyclic voltammetry experiments and numerical modeling. Fourteen parameters characterize the electrochemical reaction on a clean electrode, with the Butler-Volmer equation describing the electron transfer step to solution and to adsorption bound electroactive species. A Frumkin Isotherm describes the thermodynamics of the adsorption process. Experimentally realized anodic current densities at cell voltages below 1.23 V were circa 1 mA cm −2, a hydrogen production level far too low for commercial viability of the solar thermal decoupled water electrolysis process. However, our 3-D finite element model of the electrochemical cell operating at 318 K, suggests that current densities approaching 20 mA cm −2 can be reached in a cell with forced convection and a solvent that increases the solubility of CoO by a factor of 10 above that for KOH. Finally, the current density calculations from the perspective of industrial viability suggest producing porous metal anodes for which the actual surface area is 10–100 times larger than the electrode's planar area.